Growth and yield traits of pickling cucumber plants to measure the impact of different irrigation management practices - de Cantuário, Fernando Soares; Salomão, Leandro Caixeta; da Silva Curvêlo, Carmen Rosa; de Jesus Guimarães, João [UNESP]; Luz, José Magno Queiroz; Ferreira, Luiz Leonardo; Pereira, Alexandre Igor Azevedo (Southern Cross Publishing, 2021)
Cucumber (Cucumis sativus L) is mostly cultivated by family-based farmers worldwide and processed to pickles by small to mid-sized industries generating employment and income. But irrigation management needs better investigation for adapting adequate sustainable practices. The rational use of irrigation water still has been neglected nowadays, but can improve cucumber production. The objective was to evaluate different irrigation levels on growth and yield parameters of the Amour F1 cucumber hybrid through time under greenhouse. Treatments consisted of five irrigation levels (amounts of water applied of 62, 93, 124, 155 and 186 mm), ranging from water stress to excess water. The experimental design was randomized blocks, with four replications. Vegetative growth and yield showed different responses to the irrigation levels. Plant height and internode length were less influenced by the irrigation levels, throughout the time, than stem diameter and root length. Cucumber yield was low with 62 mm and 93 mm, higher with 124 mm irrigation, and delayed in time at 155 mm and 186 mm. Water excess (186 mm) was not beneficial for pickling cucumber plants, and the amount of 124 mm was satisfactory for their development and yield. The results of this study may allow adoption of sustainable irrigation practices with no waste of agricultural water, a scarce resource worldwide.
Keywords: Cucurbitaceae; Greenhouse; Water; Water Deficit; Water Excess